Peran Strategis Manajemen Kurikulum dalam Digitalisasi dan Pengembangan Kurikulum Merdeka di SMAN 1 Menganti - Aldwin Asandy Proboatmojo; Nabila Azahrotun Jihan; Adellia Al Muhanif; Mohammad Asril Nabawy; Ayu Wulandari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study examines the role of curriculum management in the development of the Merdeka Curriculum at SMA Negeri 1 Menganti with a focus on adaptation to digitization and 21st century learning. The research uses a qualitative approach through interviews, observations, and documentation. The findings show that Merdeka Curriculum has been implemented for four years, facing the main challenge of changing the mindset of educators and students towards student-centered learning. Other obstacles include limited mastery of technology and human resource readiness at the beginning of implementation. SMA Negeri 1 Menganti has succeeded in increasing school digitalization and utilizing information technology to support the teaching and learning process, thanks to curriculum management that is responsive to technological developments and the needs of the world of work. This research highlights the importance of innovation in curriculum management to realize relevant, adaptive and quality education in the global era.